Dynamic topography in South America - Davila, Federico Miguel (2013)
Supracrustal tectonics and mantle flow interact to create Earth's topography. While tectonics is associated with the isostatic components of topography, the deflections caused by mantle dynamics, or dynamic topography, represent the non-isostatic components. South America is an ideal natural laboratory to analyze these two contrasting components from the high Andes to the distal plains. Both regions are active and affected by complex geodynamic processes like the subduction of oceanic ridges, geometry and age of slabs, etc. These subducting anomalies affect not only the convergence dynamics and stresses along the entire margin, but also the distribution of mass anomalies in the mantle, which are the main cause of sublithospheric flow and dynamic topography. Here we revisited five examples from north to south, which demonstrate that, the Andes and the distal forelands have been uncompensated since the beginning of the Cenozoic and that additional forces, such as mantle downwellings and upwellings, are required to account for the observed topographies in basins and elevations.